(untitled) (AmeriQuests, 2012)
Law and historiography share several fundamental paradigms: the search for truth based on facts from the past; investigation; the presentation of “exhibits;” testimony and the evaluation of witnesses (according to the kind of jurisprudence that forms source criticism); the use of “pieces of evidence,” etc. If it is true that “legal principles cannot be transferred as-is into historical research,” that the demands in terms of evidence are not of the same nature, and that—and this is a decisive difference, but one that is not always observed, far from it, and it’s precisely this difference that will be the theme of my reflections today—the historian is not supposed to, having reconstructed the facts, regardless of how incriminating they are, pass judgement on, nor present a prosecutor’s charge against (nor plea for the acquittal of) figures from the past.With a belated but exceptionally violent spurt, the 1997 publication of The Black Book of Communism in France rekindled the long-lasting debate on the role and record of communism, mobilizing the press as a whole and every essayist in sight, with no signs that controversy is about to die down. Un pavé dans l’histoire, by Pierre Rigoulot and Ilios Yannakakis, recounts the first months of the polemic surrounding the “memory of communism” in France, positioning itself from the accusatory point of view of the book’s contributors. Several years later, the collective text Du passé faisons table rase! introduced French readers to the contrasting receptions The Black Book’s translations met in all of Europe’s countries and languages: very favourable in the East, reticent in the West—with intellectual France, as always, a clear exception, diverging from the countries who had known “real socialism,” despite the reluctance of a rearguard of prudently recycled apparatchiki who had preferred not to “stir up the mud” of the past.